Charging effect reduction in electron beam lithography and observation of single nanopillars on highly insulating substrates - Tirpanci, Saban; Buergler, Daniel E.; Schneider, Claus M.; Rameev, Bulat; Aktas, Bekir (Elsevier Science Bv, 2015)
Electron beam writing and imaging of nanoscale structures on highly insulating substrates severely suffer from charging effects, which cause reduction in pattern resolution, positioning precision, and imaging quality. Conductive layers deposited above or below the resist layer can effectively reduce charge accumulation, but often give rise to contamination impairing the physical and chemical properties of functional nanostructures. Here we deal with top and bottom contacted, sub-micron-sized nanopillars made from multilayer stacks comprising ferromagnetic and non-magnetic materials for the study of current-induced magnetization dynamics. We show how the charging effects in a previously established fabrication process for single-crystalline nanopillars by H. Dassow et al. (2006) [1] can be significantly reduced by using the bottom electrode layer as charge dissipater and only isolating and disconnecting the bottom electrodes from ground after the fabrication of the delicate nanopillar structure by electron beam lithography. The modified process is successfully applied to Co2MnSi/Ag/Co2MnSi(001) multilayer stacks grown on highly insulating MgO substrates. Ellipsoidal nanopillars with a cross-section of 75 x 120 nm(2) reveal 2% giant magnetoresistance and angular dependent magnetization behavior due to the magnetic anisotropy of the elliptical nanomagnets. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Charging effects; Electron beam lithography; Scanning electron microscopy; Nanopillar; Spin-transfer torque